Análise dos determinantes da reprovação das contas dos gestores municipais no Estado do Ceará - Salmito, Rachel Bessa (2018)
In response to a demand of society through the provision of public and public services for the indebtedness of public power, as well as mechanisms that seek to correct deviations. As a way of guaranteeing a recovery process, the legislative power, with the technical support of the courts of law, was given the role of overseeing the use of resources by municipal managers. As there are some irregularities, the Court of Auditors has a security application to the mayors, in the form of fines or the option of rejecting their accountability. In this way, the present work presents itself as one of the socioeconomic indicators of the municipalities that makes more and more the adequacy of exercise accounts by the Court of Accounts of the State of Ceará. In order to do so, he resorted to a discrete choice model in order to answer the questions asked about the court, based on the characteristics of the municipality. The results were the most populous, and with higher levels of investment tend to have the least rejected currents. On the other hand, the greater proportion of public resources between the population and the income inequality, are greater as chances of rejection. For example, no indicators of a reinstatement of mayors implicit in greater disapproval of their accounts were found.